2022
DOI: 10.1021/acsomega.1c06014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oxidation Resistance of Ultrafine-Grain Microstructure AlCoCrFeNi High Entropy Alloy

Abstract: This work investigates the effect of ultrafine-grain microstructure on the oxidation behavior of AlCoCrFeNi high entropy alloy (HEA). The ultrafine-grain microstructure is obtained using stationary friction processing performed at two different rotational speeds, 400 and 1800 rpm, for 5 min duration. Processed samples demonstrate high depth of refinement (DOR) and ultrafine grain size (0.43–1 μm) at high rotational speeds along with significant phase transformations from BCC/B2 to FCC microstructure. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 49 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…A series of investigations were already carried about the behavior of HEAs in high temperature oxidation. Among the studied alloys which are the closest to the Cantor composition but which are slightly different, there are Mn-free Al-containing ones (AlCoCrFeNi) [19,20], or some Ni-free ones [21,22], for instance. The oxidation behavior of the equimolar CoNiFeMnCr composition was specifically investigated in laboratory air at temperatures from 500°C to 900°C [23,24], and in synthetic air between 900 and 1100°C [25].…”
Section: Introductionmentioning
confidence: 99%
“…A series of investigations were already carried about the behavior of HEAs in high temperature oxidation. Among the studied alloys which are the closest to the Cantor composition but which are slightly different, there are Mn-free Al-containing ones (AlCoCrFeNi) [19,20], or some Ni-free ones [21,22], for instance. The oxidation behavior of the equimolar CoNiFeMnCr composition was specifically investigated in laboratory air at temperatures from 500°C to 900°C [23,24], and in synthetic air between 900 and 1100°C [25].…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation of Cr- and Al-based alloys is particularly interesting due to their good oxidation-resistance capabilities [ 16 ]. Recently, there have been more studies on the oxidation of the AlCoCrFeNi system [ 17 , 18 , 19 ]. As the composition space increases with the introduction of new HEAs, it becomes increasingly challenging to experimentally test them in variable oxidizing environments.…”
Section: Introductionmentioning
confidence: 99%
“…3 The special structure of HEAs with its excellent comprehensive properties, such as high hardness, excellent magnetic properties, outstanding oxidation resistance, superior corrosion resistance, and excellent wear resistance has a broad application prospect. [4][5][6][7][8] Although traditional soft magnetic alloys have excellent magnetic properties, there are some problems such as low strength and poor corrosion resistance. Studies have shown that HEAs are an ideal soft magnetic material with excellent soft magnetic properties and excellent mechanical properties.…”
mentioning
confidence: 99%